Micro Electro Discharge Milling for Microfabrication - Ali, Mohammad Yeakub; Reyad, Mehfuz; Khan, Ahsan Ali; Ismail, Ahmad Faris (In-Tech, 2005)
Miniaturization of product is increasingly in demand for applications in numerous fields, such as aerospace, automotive, biomedical, healthcare, electronics, environmental, communications and consumer products. Researchers have been working on the microsystems that promise to enhance health care, quality of life and economic growth. Some examples are micro-channels for micro fuel cell, lab-on-chips, shape memory alloy ‘stents’, fluidic graphite channels for fuel cell applications, miniature actuators and sensors, medical devices, etc. (Madou, 2002; Hsu, 2002). Thus, miniaturization technologies are perceived as potential key technologies. One bottleneck of product miniaturization is the lack of simpler and cheaper fabrication techniques. Currently the common techniques are based on silicon processing techniques, where silicon-based materials are processed through wet and dry chemical etching. These techniques are suitable for microelectronics, limited to few silicon-based materials and restricted to simple two dimensional (2D) or pseudo three dimensional (2.5D) planar geometries. Other fabrication processes, such as LiGA (lithography, electroforming and molding), laser, ultrasonic,focused ion beam (FIB), micro electro discharge machining (EDM), mechanical micromilling, etc. are expensive and required high capital investment. Moreover these processes are limited to selected materials and low throughput (Ehmann et al. 2002).A less expensive and simpler microfabrication technique is sought to produce commercially viable microcomponents. Micro electro discharge (ED) milling, a new branch of EDM, has potential to fabricate functional microcomponents. The influences of micro ED milling process parameters on surface roughness, tool wear ratio and material removal rate are not fully identified yet. Therefore, modeling of ED milling process parameters for surface roughness, tool wear ratio and material removal rate are necessary.